Forecasting interest rates - Gregory R. Duffee (The Johns Hopkins University, Department of Economics, 2012)
This chapter discusses what the asset-pricing literature concludes about the forecastability of interest rates. It outlines forecasting methodologies implied by this literature, including dynamic, no-arbitrage term structure models and their macro-finance extensions. It also reviews the empirical evidence concerning the predictability of future yields on Treasury bonds and future excess returns to holding these bonds. In particular, it critically evaluates theory and evidence that variables other than current bond yields are useful in forecasting. - -Term structure ; affine models ; predicting bond returns ; predicting bond yields
Keywords: G12; 330